Pengembangan Platform Digital untuk Pemasaran Produk Lokal dan Wisata Desa Senjoyo Kabupaten Semarang - Adhi Susano; Meida Rachmawati; Aswin Fitriansyah; Nunu Kustian; Retna Ningsih (Institut Teknologi dan Bisnis Semarang, 2025)
This community service aims to develop a digital platform to market local products and tourism potential in Senjoyo Village, Semarang Regency. The program was implemented using a participatory action research approach involving 30 MSME actors and tourism managers. Implementation methods include assessment, training, platform development, and intensive mentoring. The program results show an increase in digital understanding by 75%, an increase in MSME turnover by 35%, and a 45% increase in tourist visits. The Senjoyo Digital Market platform has successfully integrated 45 MSME products and 5 tour packages with a conversion rate of 8.5%. The formation of the Senjoyo Digital Community is the key to program sustainability. The main challenge in the form of digital gaps between generations can be overcome through adaptive learning approaches and mentoring systems.